Lithium cobalt oxide positive electrode material, preparation method thereof, positive electrode sheet and lithium battery

CN122992046APending Publication Date: 2026-10-27SHENZHEN HIGHPOWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611467831.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

本申请中,X元素具有三重协同功能。第一重功能为第一结构晶格梯度掺杂稳定P63mc结构,通过表层较高浓度的X掺杂抑制晶格氧逃逸和钴溶出,同时体相低浓度掺杂避免克容量牺牲。第二重功能为诱导形成共晶格过渡区域,X元素在第一结构基体表层的富集区域通过原子重构形成具有共格关系的第二结构,该过渡区域作为第一结构与第三结构之间的晶格适配器,大幅增强层间结合力和结构稳定性。第三重功能为化学键桥接外结构,第二结构中富X区域与第三结构共享X-O配位环境,通过X-O化学键网络实现第三结构与第一结构的共格连接,而非简单的物理吸附。三重功能均通过同一种X元素实现,元素复用实现多功能化设计,各功能之间形成协同效应,在提升克容量的前提下,实现能量密度、循环性能和安全性能的综合提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992046A_ABST
    Figure CN122992046A_ABST
Patent Text Reader

Abstract

The application relates to a lithium cobaltate positive electrode material, a preparation method thereof, a positive electrode sheet and a lithium battery. The lithium cobaltate positive electrode material comprises a first structure, a second structure and a third structure, the first structure is a lithium cobaltate matrix comprising at least a P63mc space group; the second structure is a co-lattice transition layer comprising at least one of Fd-3m, Fm-3m, R-3m and P63mc space groups; and the third structure is a crystalline compound comprising at least one of R-3m, Pnma, Pmn21 and C2 / c space groups. The same X element is contained in the first structure, the second structure and the third structure, and the X element is distributed in a concentration gradient increasing from inside to surface in the lattice of the first structure; the second structure is connected with the first structure through X-O chemical bond network to form Co-O-X coherent matching, and is connected with the third structure through X-O bond. The scheme provided by the application can comprehensively improve the energy density, the cycle performance and the safety performance under the premise of improving the gram capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium battery technology, and in particular to lithium cobalt oxide cathode materials, their preparation methods, cathode sheets, and lithium batteries. Background Technology

[0002] Lithium-ion batteries are widely used in consumer electronics due to their high energy density and long cycle life. Lithium cobalt oxide (LiCoO2), as the mainstream cathode material, suffers severe structural degradation in its commercially available R-3m structure when the charging voltage exceeds 4.5 V, accompanied by lattice oxygen escape and cobalt dissolution, significantly increasing the risk of thermal runaway. The novel P63mc structure lithium cobalt oxide, with its more stable crystal structure and higher energy density, is considered a strong contender for next-generation high-voltage lithium cobalt oxide. However, the P63mc structure is metastable, undergoing an irreversible phase transition to the R-3m structure at temperatures above 280℃, resulting in poor intrinsic stability.

[0003] In related technologies, single-element uniform doping or surface coating are used for improvement. However, single-element uniform doping is difficult to uniformly relieve stress, and excessive doping will sacrifice specific capacity. Conventional surface coating has weak bonding with the substrate interface, which can easily lead to bulk and interface failure under long-term cycling and high-temperature conditions, which is not conducive to the development of lithium batteries with high energy density, long cycle performance and high safety performance.

[0004] Therefore, there is an urgent need to develop a new type of lithium cobalt oxide material that can comprehensively improve energy density, cycle performance, and safety performance while increasing specific capacity. Summary of the Invention

[0005] To address or partially address the problems existing in related technologies, this application provides a lithium cobalt oxide cathode material, its preparation method, cathode sheet, and lithium battery, which can achieve a comprehensive improvement in energy density, cycle performance, and safety performance while increasing specific capacity.

[0006] The first aspect of this application provides a lithium cobalt oxide cathode material, wherein the lithium cobalt oxide cathode material has a three-layer core-shell structure, comprising: A first structure, wherein the first structure comprises at least a lithium cobalt oxide matrix of space group P63mc; A second structure, which at least partially covers the first structure, includes a co-lattice transition layer of one or more structures in the space groups Fd-3m, Fm-3m, R-3m, and P63mc. A third structure, which at least partially covers the second structure, comprises a crystalline compound of one or more of the space groups R-3m, Pnma, Pmn21, and C2 / c. The first, second, and third structures all contain the same element X. The concentration of element X increases progressively from the distal end to the proximal end of the second structure within the lattice of the first structure. The second structure forms a Co-OX coherent match with the first structure via an XO chemical bond network and also forms an XO bond with the third structure. The element X is at least one of Al, P, Zr, Ti, La, and Y. In the first structure, the concentration of element X from the distal end to the proximal end of the second structure is 0~2 at.%; the total concentration of element X in the lithium cobalt oxide cathode material is less than 5 at.%; the thickness of the second structure is 5nm~30nm; the thickness of the third structure is 2nm~20nm; the second structure is a Li-Co-XO structure containing element X, where element X occupies a portion of the lattice sites; the second structure and the third structure form a continuous XOX or XO-Li chemical bond network.

[0007] A second aspect of this application provides a method for preparing a lithium cobalt oxide cathode material, comprising the following steps: S1. Sodium source, cobalt source and first compound containing element X are mixed in stoichiometric ratio and sintered at high temperature under first set conditions to obtain sodium cobaltate of phase P2. The concentration of element X in sodium cobaltate of phase P2 increases in a gradient from the inside to the outside. S2. The product obtained in S1 is mixed with lithium salt and subjected to ion exchange reaction under the second set conditions to obtain lithium cobalt oxide with a P63mc space group structure containing an X element gradient distribution, which is used as the first structure. S3. The product obtained in S2 is dispersed in a solvent, a lithium source and a second compound containing element X are added, and after stirring and evaporation, it is subjected to low-temperature sintering under a third set condition. A co-lattice transition layer containing at least one or more of the space groups Fd-3m, Fm-3m, R-3m, and P63mc is formed in situ on the surface of the first structure as the second structure. At the same time, a crystalline compound coating layer containing at least one or more of the space groups R-3m, Pnma, Pmn21, and C2 / c is formed in situ on the surface of the second structure as the third structure. The first compound containing element X and the second compound containing element X are each independently selected from compounds containing element X, and the two contain the same element X.

[0008] In some embodiments of the present invention, the first set conditions include: a high-temperature sintering temperature of 720°C to 880°C and a high-temperature sintering time of 18h to 48h.

[0009] In some embodiments of the present invention, the second set conditions include: an ion exchange temperature of 80°C to 140°C and an ion exchange time of 8h to 72h; and / or, in S3, the stirring and evaporation temperature is 100°C to 130°C.

[0010] In some embodiments of the present invention, the low-temperature sintering temperature in the third setting condition is lower than the temperature at which the P63mc space group structure undergoes an irreversible phase transition to the R-3m space group structure.

[0011] In some embodiments of the present invention, the third set conditions include: the temperature of low-temperature sintering is 150°C to 250°C, and the time of low-temperature sintering is 4h to 24h.

[0012] In some embodiments of the present invention, in step S1, the stoichiometric ratio of the sodium source, the cobalt source and the first compound containing element X satisfies the following: the molar ratio of Na:Co:X is (0.6~0.9):1:a, 0<a≤0.1.

[0013] In some embodiments of the present invention, in S1, the equilibrium solid solubility of the X element in the lattice of the P2 phase sodium cobaltate is less than 0.5 at.

[0014] In some embodiments of the present invention, in step S3, the amount of lithium source and the second compound containing element X added satisfies the following condition: the molar ratio of element X to Co is (0.005:1) to (0.02:1).

[0015] In some embodiments of the present invention, in step S3, the mass of the crystalline compound coating layer is 0.5% to 2% of the mass of the first structural matrix.

[0016] In some embodiments of the present invention, in S1 and S3, the X element is at least one of Al, P, Zr, Ti, La, and Y.

[0017] A third aspect of this application provides a positive electrode sheet, which comprises the aforementioned lithium cobalt oxide positive electrode material, or comprises lithium cobalt oxide positive electrode material prepared by the aforementioned preparation method.

[0018] A fourth aspect of this application provides a lithium battery comprising the aforementioned positive electrode.

[0019] The technical solution provided in this application may include the following beneficial effects: In this application, element X possesses three synergistic functions. The first function is to stabilize the P63mc structure through gradient doping of the first structure lattice. The high concentration of X doping on the surface suppresses lattice oxygen escape and cobalt dissolution, while the low concentration of doping in the bulk phase avoids capacity loss. The second function is to induce the formation of a co-lattice transition region. The enriched region of X element on the surface of the first structure matrix forms a second structure with a coherent relationship through atomic reconstruction. This transition region acts as a lattice adapter between the first and third structures, significantly enhancing interlayer bonding and structural stability. The third function is to bridge the external structure through chemical bonds. The X-rich region in the second structure shares the XO coordination environment with the third structure, achieving a coherent connection between the third and first structures through an XO chemical bond network, rather than simple physical adsorption. All three functions are achieved using the same element X. Element reuse enables a multifunctional design, and the functions create a synergistic effect, resulting in a comprehensive improvement in energy density, cycle performance, and safety performance while increasing specific capacity.

[0020] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit this application. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the structure of Example 1.

[0022] Figure 2 The X-ray diffraction (XRD) patterns are for Example 1 and Comparative Example 1.

[0023] Figure 3 This is the X-ray photoelectron spectroscopy (XPS) etching pattern of Example 1.

[0024] Figure 4 The differential scanning calorimetry (DSC) curves for Example 1 and Comparative Example 1 are shown.

[0025] Figure 5 This is a scanning electron microscope (SEM) image of Example 1.

[0026] Figure 6 The first-week charge-discharge curves are for Example 1 and Comparative Example 1.

[0027] Figure 7 The graphs show the cyclic performance of Example 1 and Comparative Example 1. Detailed Implementation

[0028] The embodiments of this application will now be described in more detail. It should be understood that this application may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to make this application more thorough and complete, and to fully convey the scope of this application to those skilled in the art.

[0029] The terminology used in this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The singular forms “a,” “the,” and “the” used in this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used herein refers to and includes any or all possible combinations of one or more of the associated listed items.

[0030] It should be understood that although the terms "first," "second," "third," etc., may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish information of the same type from one another. For example, without departing from the scope of this application, first information may also be referred to as second information, and similarly, second information may also be referred to as first information. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0031] P63mc lithium cobalt oxide is a metastable phase, undergoing an irreversible phase transition to the R-3m structure at temperatures above 280℃, exhibiting poor intrinsic stability. Related technologies employ single-element homogeneous doping or surface coating for improvement; however, homogeneous doping with a single element is insufficient for uniform stress relief, and excessive doping sacrifices specific capacity. Conventional surface coatings exhibit weak interfacial bonding with the substrate, easily leading to bulk and interfacial failures under long-term cycling and high-temperature conditions, hindering the development of lithium batteries with high energy density, long cycle performance, and high safety. Therefore, there is an urgent need to develop a novel lithium cobalt oxide material that can comprehensively improve energy density, cycle performance, and safety performance while increasing specific capacity.

[0032] To address the aforementioned issues, this application provides a lithium cobalt oxide cathode material that can comprehensively improve energy density, cycle performance, and safety performance while increasing specific capacity.

[0033] This application provides a lithium cobalt oxide cathode material with a three-layer core-shell structure, including a first structure, a second structure, and a third structure. The first structure is a lithium cobalt oxide matrix containing at least the P63mc space group. The second structure at least partially covers the first structure and contains at least one or more co-lattice transition layers of the space groups Fd-3m, Fm-3m, R-3m, and P63mc. The third structure at least partially covers the second structure and contains at least one or more crystalline compounds of the space groups R-3m, Pnma, Pmn21, and C2 / c. The first, second, and third structures each contain at least the same X element, and the X element exhibits an increasing concentration gradient from the inside to the outside within the lattice of the first structure. The second structure forms a Co-OX co-lattice match with the first structure and an XO bond with the third structure through an XO chemical bond network.

[0034] In this embodiment, the P63mc space group belongs to a polar non-centrosymmetric structure in the hexagonal crystal system, and its oxygen layer stacking sequence is ABAC, which differs from the ABCABC stacking sequence of conventional R-3m space group lithium cobalt oxide. P63mc structure lithium cobalt oxide exhibits higher specific capacity and energy density, meeting the requirements of high-voltage charge and discharge. The first structure, as the core of the entire material, undertakes the main functions of lithium-ion storage and deintercalation; its structural integrity and stability directly affect the electrochemical performance of the material. However, the P63mc structure is a metastable phase with insufficient intrinsic stability, requiring reinforcement through subsequent structural design.

[0035] The second structure comprises at least one or more of the following space groups: Fd-3m, Fm-3m, R-3m, and P63mc, forming a commutative lattice transition layer. The Fd-3m space group corresponds to a defective spinel-like structure, the Fm-3m space group to a rock salt phase structure, the R-3m space group to a layered O3 phase structure, and the P63mc space group is the same as that of the first structure. The function of the second structure is to act as a lattice-matching and stress-buffering layer between the first and third structures. It forms atomic-scale lattice continuity with the structures on both sides through commutative lattice matching, rather than physically isolating the interface. Commuative lattice matching refers to adjacent phases having similar lattice parameters and atomic arrangements at the interface, allowing atoms to be continuously arranged at the interface without generating a large number of mismatched dislocations. Through commutative lattice matching, the second structure effectively releases the lattice mismatch stress between the first and third structures, preventing severe lattice distortion and crack initiation at the interface.

[0036] The third structure comprises at least one or more crystalline compounds from the R-3m, Pnma, Pmn21, and C2 / c space groups. The Pnma and Pmn21 space groups correspond to orthorhombic compounds, such as orthorhombic lithium phosphate, which has the Pmn21 space group; the C2 / c space group corresponds to monoclinic compounds. As the outermost crystalline compound coating layer, the third structure functions to physically isolate the electrolyte to suppress interfacial side reactions, provide lithium-ion conduction channels, achieve lithium replenishment, and form a thermodynamically stable protective shell. This crystalline compound coating layer has a complete crystalline structure, rather than being amorphous or amorphous, thus exhibiting higher chemical stability and mechanical strength. Furthermore, as a solid electrolyte layer, this crystalline compound coating layer has good compatibility with semi-solid-state or all-solid-state batteries, and can reduce polarization and impedance.

[0037] Within the lattice of the first structure, the concentration of element X increases from the inside to the outside. Specifically, the concentration of X is low, even close to zero, in the internal region of the first structure, while it is high in the surface region. The formation mechanism of this gradient distribution can be attributed to the following: During high-temperature solid-state sintering, X diffuses from the particle surface inwards. However, due to the low equilibrium solid solubility of X in the lithium cobalt oxide lattice, once the X content in the bulk phase reaches the solid solubility limit, excess X cannot continue to enter the lattice and instead segregates to the particle surface and grain boundaries. This spontaneously forms a steady-state gradient distribution with increasing concentration from the far end of the second structure (the region far from the second structure, i.e., the internal region of the first structure) to the near end of the second structure (the region close to the second structure, i.e., the surface region of the first structure). This gradient distribution has the following synergistic functions: low-concentration X doping in the bulk phase stabilizes the P63mc structure without significantly sacrificing specific capacity, while the high-concentration X-rich region on the surface provides chemical bond anchors for the subsequent construction of the second and third structures.

[0038] XO chemical bonds refer to the chemical bonds formed between element X and oxygen, possessing high bond energy. Co-OX coherent matching refers to the connection at the interface between the first and second structures, where the Co-O bonds formed by cobalt and oxygen and the XO bonds formed by element X and oxygen are linked through shared oxygen atoms, forming a continuous Co-OX bonding network. This coherent matching enables atomic-scale lattice continuity between the first and second structures at the interface, rather than simple physical contact or weak chemisorption. The XO bonding between the second and third structures refers to the continuous extension of the chemical bonds formed by element X and oxygen at the interface, achieving chemical bond bridging between the second and third structures. Through the construction of the above XO chemical bond network, a continuous eutectic interface is formed between the first, second, and third structures. The multiphase interface bonding force is much stronger than conventional physical adhesion or weak chemisorption, thus effectively suppressing interface peeling and failure under long-term cycling and high-temperature conditions.

[0039] In this embodiment, element X possesses three synergistic functions. The first function is to stabilize the P63mc structure through a lattice gradient distribution in the first structure. The high concentration of X doping on the surface suppresses lattice oxygen escape and cobalt dissolution, while the low concentration distribution in the first structure avoids severe capacity loss. The second function is to induce the formation of a co-lattice transition region. In the enriched region of X element on the surface of the first structure matrix, atomic reconstruction forms a second structure with a coherent relationship. This transition region acts as a lattice adapter between the first and third structures, significantly enhancing interlayer bonding and structural stability. The third function is a chemical bond bridging structure. The X-rich region in the second structure shares the XO coordination environment with the third structure, achieving a coherent connection between the third and first structures through an XO chemical bond network, rather than a simple physicochemical adhesion. All three functions are achieved using the same element X. Element reuse enables a multifunctional design, and the functions create a synergistic effect, achieving a comprehensive improvement in energy density, cycle performance, and safety performance while increasing specific capacity.

[0040] In some embodiments of the present invention, element X is at least one of Al, P, Zr, Ti, La, and Y.

[0041] These elements possess suitable ionic radii and strong oxygen affinity, enabling them to form stable lattice sites in the lithium cobalt oxide lattice, which is beneficial for constructing a coherently matched chemical bond network. Al and P elements have smaller ionic radii, readily entering cobalt sites or interstitial sites in the lithium cobalt oxide lattice, with P being the most readily incorporated. 5+ Existing in the form of oxygen, it possesses high diffusion and migration capabilities within the crystal lattice. Zr, Ti, La, and Y elements have high oxygen affinity, enabling them to form stable XO chemical bonds and enhance interfacial bonding strength. Taking P as an example, during high-temperature sintering, P... 5+Diffusion from the particle surface to the interior, constrained by the layered structure of CoO6 octahedra, affects P. 5+ The lattice has limited capacity, and the near-surface region quickly reaches solid solution saturation. Subsequent diffused phosphorus (P) cannot be contained by the lattice and is forced to segregate at the grain surface and grain boundaries. With prolonged sintering time, the P concentration in the bulk phase is constrained to a low level by the solid solution limit, while the surface region continues to accumulate P due to segregation, ultimately forming a steady-state gradient distribution from high concentration on the surface to low concentration in the bulk. The key feature of this gradient structure is that the concentration of x in the bulk phase is controlled below the solid solution limit, without affecting the integrity of the layered structure; while the x-rich region on the surface acts as a functional layer for inducing and chemically bridging subsequent crystalline compound coating layers.

[0042] In some embodiments of the present invention, in the first structure, the concentration of element X in the direction from the distal end of the second structure to the proximal end of the second structure is 0~2 at.%.

[0043] This concentration range refers to the continuous increasing distribution of X element doping concentration from the internal region to the outer surface region of the first structure. The doping concentration in the core region can approach 0, meaning that the interior is almost free of X element doping, ensuring that the core region of the P63mc structure maintains its intrinsic high capacity characteristics. The doping concentration in the surface region can reach up to 2 at.%, meaning that the proportion of lattice sites occupied by X element at the outermost surface of the first structure is up to 2 at.%. On the one hand, doping concentrations higher than 2 at.% will cause significant lattice distortion, destroying the integrity of the P63mc structure and reducing structural stability; on the other hand, doping concentrations exceeding this limit will excessively occupy electrochemical active sites, blocking lithium ion insertion / extraction channels, leading to a significant decrease in specific capacity.

[0044] It should be noted that this concentration range is a relative concentration measured in atomic percentages. Specific values ​​can be determined using methods such as X-ray photoelectron spectroscopy (XPS), energy dispersive spectroscopy (EDS), electron probe microscopy (EPM), or transmission electron microscopy combined with EDS. XPS can peel away layers of the material surface and determine the elemental content at each depth, thereby obtaining a concentration distribution curve of X-rays from the surface inwards.

[0045] In some embodiments of the present invention, the total doping concentration of element X in the lithium cobalt oxide cathode material is less than 5 at.%.

[0046] The total doping concentration refers to the doping concentration of element X in the entire lithium cobalt oxide cathode material. When the total doping concentration of element X is below 5 at.%, the high specific capacity of the lithium cobalt oxide matrix can be maintained to the greatest extent while ensuring structural stability. When the total doping concentration reaches or exceeds 5 at.%, the excessive element X will occupy a large number of lithium-ion transport channels and electrochemical active sites, resulting in a significant reduction in the reversible specific capacity of the material. At the same time, excessive doping may induce the precipitation of impurity phases, destroying the integrity of the layered structure of the material.

[0047] It should be noted that, since the distribution of element X in the bulk phase and near the surface is not uniform, the total doping concentration can be the weighted average of the concentrations in each region. Therefore, even if the total doping concentration is less than 5 at.%, the doping concentration in a local area of ​​the surface layer may still reach 2 at.%, while the doping concentration inside the bulk phase is much lower than the average value.

[0048] In some embodiments of the present invention, the thickness of the second structure is 5 nm to 30 nm.

[0049] If the thickness of the second structure is less than 5 nm, the spatial scale of the commutative lattice transition layer is insufficient to adequately buffer the lattice mismatch stress between the first and third structures. The stress release and lattice adaptation functions of the transition layer are difficult to fully realize, and high strain energy will still accumulate at the interface, easily leading to dislocation multiplication and interface cracking during long-term cycling. If the thickness of the second structure is greater than 30 nm, it increases the migration path length of lithium ions across the interface layer, resulting in a significant increase in interface impedance, which is detrimental to the rate performance and specific capacity of the material. Furthermore, an excessively thick transition layer introduces more lattice defects and grain boundaries, thus reducing structural stability. Within the thickness range of 5 nm to 30 nm, the commutative lattice transition layer has sufficient spatial scale to accommodate and release interface mismatch stress without significantly hindering lithium ion interfacial transport, achieving the optimal balance between structural stability and electrochemical performance.

[0050] The thickness of the second structure can be observed and measured by transmission electron microscopy of the material cross-section. Specifically, at least 20 measurement points are randomly selected in multiple fields of view, and the average value is taken as the thickness of the layer. This thickness can be adjusted by controlling the amount of lithium source and X-containing compound added in the preparation method, as well as the temperature and time of low-temperature sintering.

[0051] In some embodiments of the present invention, the thickness of the third structure is 2nm to 20nm.

[0052] If the thickness of the third structure is less than 2 nm, it is difficult to form a continuous and complete crystalline compound coating layer. The coating layer may be distributed as discontinuous islands or particles on the surface of the second structure. The electrolyte can still directly contact the internal structure through coating defects, triggering interfacial side reactions and cobalt dissolution. The physical isolation and chemical protection functions of the coating layer cannot be fully utilized. If the thickness of the third structure is greater than 20 nm, it will significantly increase the diffusion barrier of lithium ions in the coating layer. Lithium ions need to cross a thicker solid electrolyte layer to reach the substrate surface, resulting in a significant increase in interfacial impedance and a deterioration in the rate performance of the material. At the same time, an excessively thick inactive coating layer will reduce the overall mass energy density of the material. Within the thickness range of 2 nm to 20 nm, the crystalline compound coating layer can form a uniform and complete covering layer, effectively isolating the electrolyte from direct contact with the substrate. At the same time, the lithium ion conductivity of the coating layer itself can ensure the smooth passage of lithium ions, achieving the best balance between protection and transport performance.

[0053] The thickness of the third structure can be observed and measured by transmission electron microscopy of the material cross-section. Specifically, at least 20 measurement points are randomly selected in multiple fields of view, and the average value is taken as the thickness of the layer. This thickness can be adjusted by controlling the amount of the compound containing element X in the preparation method, as well as the temperature and time of low-temperature sintering.

[0054] In some embodiments of the present invention, the second structure is a Li-Co-XO structure containing the element X, wherein the element X occupies a portion of the lattice sites.

[0055] The Li-Co-XO structure refers to a second structure whose basic chemical composition includes lithium, cobalt, X, and oxygen, and whose crystal structure maintains a layered or quasi-layered framework. The presence of X as a partial lattice site in the second structure can mean two things: first, X replaces cobalt in the lattice, forming a substitution solid solution; second, X enters interstitial positions, forming an interstitial solid solution. In the case of P doping, P... 5+ The X element primarily occupies cobalt sites for substitution doping. After occupying some lattice sites, it causes local changes in lattice parameters and reconstruction of atomic arrangement. However, overall, the second structure maintains its crystallographic symmetry relationship with the first structure's P63mc phase or with the related phase of the third structure, thus satisfying the crystallographic conditions for coherent matching. This Li-Co-XO structure maintains a good coherent relationship with the first structure's P63mc phase and can also form chemical bonds with the third structure, acting as both a bridge and a buffer.

[0056] In some embodiments of the present invention, the second structure and the third structure form an XOX or XO-Li continuous chemical bond network.

[0057] The XOX continuous bond network refers to the XO bond formed between the X element and oxygen element at the interface between the second and third structures, which extends continuously across the interface. That is, the XO bonds in the second and third structures are connected through shared oxygen atoms, forming a continuous XOX bond sequence. The XO-Li continuous bond network refers to the connection between the XO bond in the second structure and the lithium element in the third structure, forming an XO-Li bond through oxygen atoms. The construction of this continuous bond network relies on the presence of the same X element in both the second and third structures, resulting in similar XO coordination environments on both sides of the interface. This allows atoms to be continuously arranged at the interface without bond breakage or dangling bonds.

[0058] This continuous chemical bond network can significantly enhance the interlayer bonding force between the second and third structures, making the interfacial bonding strength much higher than that of conventional physical contact or weak chemisorption. During long-term charge-discharge cycles, the continuous chemical bond network can effectively prevent interfacial delamination and delamination failure. The continuous XO coordination environment helps to reduce the migration energy barrier of lithium ions at the interface, promoting the rapid transport of lithium ions between the second and third structures. The chemical bond network can suppress interdiffusion and side reactions at the interface, improving the chemical stability of the interface.

[0059] Corresponding to the aforementioned application function implementation method embodiments, this application also provides a method for preparing lithium cobalt oxide cathode material, cathode sheet, lithium battery, and corresponding embodiments.

[0060] This application also provides a method for preparing a lithium cobalt oxide cathode material, including the following steps: S1. Sodium source, cobalt source and the first compound containing element X are mixed in stoichiometric ratio and sintered at high temperature under the first set conditions to obtain sodium cobaltate of phase P2. The concentration of element X in sodium cobaltate of phase P2 increases in a gradient from the inside to the outside.

[0061] Sodium source refers to a compound that can provide sodium, including but not limited to at least one sodium-containing compound such as sodium carbonate, sodium hydroxide, sodium nitrate, sodium chloride, and sodium sulfate. Cobalt source refers to a compound that can provide cobalt, including but not limited to at least one cobalt-containing compound such as cobalt tetroxide, cobalt trioxide, cobalt carbonate, cobalt hydroxide, cobalt chloride, cobalt sulfate, and cobalt nitrate. The first type of compound containing element X refers to a compound containing at least one of Al, P, Zr, Ti, La, and Y. For example, when element X is P, compounds containing element P include but are not limited to at least one phosphorus-containing compound such as ammonium dihydrogen phosphate, phosphoric acid, diammonium hydrogen phosphate, ammonium phosphate, and phosphorus pentoxide. P2 phase sodium cobaltate is a layered transition metal oxide with a hexagonal crystal structure. Its interlayer can accommodate sodium ions and is suitable as a precursor for subsequent ion exchange reactions. In this high-temperature sintering process, by controlling parameters such as sintering temperature and time, the diffusion kinetics of element X are regulated, so that element X forms a gradient distribution with gradually increasing concentration from the inside to the surface in the sodium cobaltate grains. Because the equilibrium solid solubility of element X in the P2 phase sodium cobalt oxide lattice is low, excess element X cannot enter the lattice interior but instead segregates on the particle surface and grain boundaries, thus spontaneously forming a gradient distribution with increasing concentration from the inside to the surface. This gradient distribution does not require additional artificial control; it is achieved spontaneously through the surface segregation effect driven by solid solubility limitation, offering advantages such as simple process and ease of industrial scale-up.

[0062] S2. The product obtained in S1 is mixed with lithium salt and subjected to ion exchange reaction under the second set conditions to obtain lithium cobalt oxide with X gradient distribution in space group P63mc, which is used as the first structure.

[0063] Lithium salts are compounds that can provide lithium, including but not limited to at least one of lithium-containing compounds such as lithium hydroxide, lithium chloride, lithium nitrate, lithium acetate, lithium sulfate, and lithium carbonate. This ion exchange reaction utilizes lithium ions to replace sodium ions between the layers of sodium cobalt oxide, achieving complete exchange of sodium ions to lithium ions while maintaining the layered framework structure. Ion exchange is a topological chemical reaction, meaning that the main crystal lattice framework remains unchanged during the reaction, with only interlayer cations being replaced. Due to the topological chemical characteristics of the ion exchange reaction, the X element gradient distribution formed in step S1 is preserved and completely inherited into the product lithium cobalt oxide during the ion exchange process, without being homogenized or disappearing due to ion exchange. By controlling the temperature and time of the ion exchange reaction, it can be ensured that sodium ions are fully replaced by lithium ions, thereby obtaining pure-phase P63mc structured lithium cobalt oxide.

[0064] S3. The product obtained in S2 is dispersed in a solvent, a lithium source and a second compound containing element X are added, and after stirring and evaporation, it is subjected to low-temperature sintering under a third set condition. A eutectic transition layer containing at least one or more of the space groups Fd-3m, Fm-3m, R-3m, and P63mc is formed in situ on the surface of the first structure as the second structure. At the same time, a crystalline compound coating layer containing at least one or more of the space groups R-3m, Pnma, Pmn21, and C2 / c is formed in situ on the surface of the second structure as the third structure. The first compound containing element X and the second compound containing element X are each independently selected from compounds containing element X, and the two contain the same element X.

[0065] The solvent refers to a liquid medium capable of dispersing lithium cobalt oxide particles and dissolving the lithium source and the second compound containing element X, including but not limited to at least one of solvents such as deionized water, anhydrous ethanol, and acetone. The lithium source refers to a compound added in step S3 that can provide lithium, including but not limited to at least one of lithium-containing compounds such as lithium hydroxide, lithium chloride, lithium nitrate, lithium acetate, lithium sulfate, and lithium carbonate.

[0066] The second compound containing element X in S3 may be the same as or different from the first compound containing element X in S1, but they must contain the same element X. For example, when element X is element P, the first compound containing element X may be selected from ammonium dihydrogen phosphate, and the second compound containing element X may be selected from phosphoric acid; or, both may be selected from ammonium dihydrogen phosphate.

[0067] In-situ formation means that the second and third structures are grown directly on the surface of the first structure matrix through a chemical reaction, rather than by physically attaching pre-prepared coating materials to the matrix surface. The advantage of in-situ growth is that the layers are connected at the atomic scale through chemical bonds, forming coherent or semi-coherent interfaces, and the interfacial bonding force is much stronger than that of physical attachment methods.

[0068] During the low-temperature sintering process, the X element in the X-rich region of the first structure surface reacts chemically with the added lithium source and the second X-containing compound. First, a coherent transition layer of the second structure is formed on the surface of the first structure. Then, a further reaction occurs on the surface of the second structure to form a crystalline compound third structure coating layer. The low-temperature sintering temperature is strictly controlled below the temperature at which the P63mc structure undergoes an irreversible phase transition to the R-3m structure, ensuring that the metastable P63mc phase of the first structure is not destroyed during the surface modification process.

[0069] In this preparation method, the establishment of the gradient distribution of element X occurs in the high-temperature sintering stage of step S1, while the in-situ formation of the second and third structures occurs in the low-temperature sintering stage of step S3. Both stages use the same element, which includes at least X, so that element X exists and plays a role in all three layers, achieving continuous chemical bond connection from the bulk phase to the surface.

[0070] In some embodiments of the present invention, the first set conditions include: a high-temperature sintering temperature of 720°C to 880°C and a high-temperature sintering time of 18h to 48h.

[0071] If the temperature is below 720℃, the activation energy provided by the solid-state reaction is insufficient, the reaction between the sodium source, cobalt source and the first compound containing element X is incomplete, a large amount of unreacted precursor remains in the product, the crystallinity of the P2 phase layered structure is low, the element X cannot effectively enter the lattice to form doping, and the gradient distribution is difficult to establish. If the temperature is above 880℃, abnormal grain growth and over-sintering occur, the particle size distribution is uneven, and the diffusion rate of element X at high temperatures is too fast, which may cause the originally formed concentration gradient to be homogenized and disappear. In addition, excessively high temperatures can also cause some components to volatilize, changing the stoichiometry of the material.

[0072] If the sintering time is less than 18 hours, the solid-phase diffusion reaction is insufficient, the grain growth is incomplete, and the gradient distribution of element X has not yet reached a steady state. If the sintering time is more than 48 hours, the excessive grain growth leads to a decrease in the electrochemical activity of the material. At the same time, the long-term high-temperature treatment increases the process cost and energy consumption, and the gradient distribution of element X may be weakened due to continuous diffusion.

[0073] In some embodiments of the present invention, the second set conditions include: an ion exchange temperature of 80°C to 140°C and an ion exchange time of 8h to 72h.

[0074] This temperature range provides the appropriate chemical potential and activation energy for the lithium-ion substitution of sodium ions, allowing the ion exchange reaction to proceed at an acceptable rate. Below 80°C, the ion exchange rate is too slow, making complete sodium ion substitution difficult even with extended exchange times. Above 140°C, the metastable P63mc phase may undergo an irreversible phase transition to the R-3m phase at higher temperatures. Furthermore, excessively high temperatures can lead to changes in the valence state of cobalt in the lithium cobalt oxide framework and the loss of oxygen.

[0075] When the ion exchange time is less than 8 hours, the replacement of sodium ions is incomplete, and the P2 phase sodium cobalt oxide impurity phase remains in the product. When the ion exchange time is more than 72 hours, further extending the exchange time has limited contribution to improving the exchange rate. Instead, it increases the process cycle and energy consumption. Moreover, long-term treatment in the liquid phase may cause some lithium cobalt oxide to undergo hydrolysis or other side reactions, and may even increase the degree of atomic mixing inside the crystal lattice.

[0076] In some embodiments of the present invention, in step S3, the stirring and evaporation temperature is 100°C to 130°C.

[0077] This temperature range allows for efficient solvent removal, enabling the lithium source and the X-containing compound to uniformly coat the surface of the first-structure matrix particles. If the evaporation temperature is below 100°C, the solvent evaporation rate is too slow, the drying time is too long, and the coating precursor may be unevenly distributed due to incomplete precipitation. If the evaporation temperature is above 130°C, the coating precursor may decompose or agglomerate prematurely due to localized overheating before the solvent is completely evaporated, affecting the in-situ formation quality of the second and third structures during subsequent low-temperature sintering. Within the temperature range of 100°C to 130°C, the solvent evaporates at a moderate rate, and the coating precursor precipitates uniformly and adheres to the particle surface, providing a good precursor state for subsequent low-temperature sintering.

[0078] In some embodiments of the present invention, the low-temperature sintering temperature in the third setting condition is lower than the temperature at which the P63mc space group structure undergoes an irreversible phase transition to the R-3m space group structure.

[0079] The irreversible phase transition temperature refers to the lowest temperature at which lithium cobalt oxide with a P63mc structure begins to undergo an irreversible structural transformation to an R-3m structure when heated. This temperature is approximately 280℃.

[0080] Preferably, the third set conditions include: the low-temperature sintering temperature is 150℃~250℃, and the low-temperature sintering time is 4h~24h.

[0081] On the one hand, this temperature range is below the irreversible phase transition threshold of 280℃, which can strictly protect the P63mc metastable phase of the first structure from being destroyed during surface treatment; on the other hand, this temperature range can provide sufficient activation energy for surface chemical reactions, so that the X-rich region on the surface of the first structure reacts with the added lithium source and X-containing compounds to form the second and third structures in situ.

[0082] If the low-temperature sintering temperature is below 150℃, the activation energy of the surface chemical reaction is insufficient, the formation of the second and third structures is incomplete, and a continuous chemical bond network cannot be formed between the coating layer and the matrix. The coating layer may exist in an amorphous or non-crystalline state instead of the desired crystalline compound. If the low-temperature sintering temperature is above 250℃, although the surface reaction is more complete, it is close to the phase transformation threshold of 280℃, the process window is too narrow, and the risk of temperature fluctuations increases. Once the local temperature exceeds the phase transformation temperature, it will lead to an irreversible transformation of the P63mc phase of the first structure to the R-3m phase, destroying the core-shell structure design of the material.

[0083] If the sintering time is less than 4 hours, the surface chemical reaction is not yet complete, the thickness of the second and third structures is insufficient, the crystallinity is low, and the coherent interface is not fully formed. If the sintering time is more than 24 hours, the reaction is already fully completed, and further extending the sintering time will have limited contribution to structural improvement. On the contrary, it may cause sintering agglomeration between grains and increase the process cycle and energy consumption.

[0084] In some embodiments of the present invention, in S1, the stoichiometric ratio of the sodium source, the cobalt source and the first compound containing element X satisfies the following: the molar ratio of Na:Co:X is (0.6~0.9):1:a, 0<a≤0.1.

[0085] The stoichiometric ratio refers to the molar ratio of sodium, cobalt, and X elements during feeding. The theoretical range of sodium content in P2 phase sodium cobaltate is approximately 0.6 to 0.9 moles of sodium per mole of cobalt. Controlling the sodium-cobalt ratio within the range of 0.6 to 0.9 ensures the acquisition of a pure-phase P2 layered structure after high-temperature sintering, avoiding the formation of impurity phases due to excessively low sodium content or the alteration of interlayer stacking due to excessively high sodium content.

[0086] The molar ratio of element X to element cobalt is a:1, 0<a≤0.1: When the molar ratio of element X to element cobalt exceeds 0.1:1, the excess element X cannot enter the crystal lattice and will form a large number of inactive second phases at the grain boundaries, which will reduce the structural uniformity and electrochemical performance of the material; when a is 0, it is equivalent to not adding element X, and the gradient doping effect cannot be achieved.

[0087] It should be noted that, due to the low equilibrium solid solubility of element X in the sodium cobaltate lattice, most of the element X in the feed ratio eventually segregates to the particle surface and grain boundaries, with only a small amount of element X entering the lattice to form bulk doping.

[0088] In some embodiments of the present invention, in step S1, the equilibrium solid solubility of element X in the P2 phase sodium cobaltate lattice is less than 0.5 at.

[0089] Equilibrium solid solubility refers to the maximum concentration of element X that can stably exist in a solid solution form within a P2-phase sodium cobaltate lattice under given temperature and pressure conditions. A solid solubility below 0.5 at.% means that the maximum amount of element X that can be stably accommodated by the lattice in the layered structure of P2-phase sodium cobaltate is less than five-thousandths of the molar mass of cobalt. This low solid solubility is the key thermodynamic basis for the spontaneous formation of element X through gradient doping. Because the equilibrium solid solubility is below 0.5 at.%, during high-temperature sintering, element X diffusing from the particle surface to the interior quickly saturates the lattice in the near-surface region. Once the near-surface solid solubility reaches its saturation limit, any further diffusion of element X from the outside cannot be accommodated by the lattice and is forced to segregate at the particle surface and grain boundaries.

[0090] This solubility-limited segregation effect results in a significant spatial inhomogeneity in the distribution of element X within the grains: inside the grains, due to their distance from the surface and longer diffusion distance, the concentration of element X is constrained by the solubility limit to a low level below 0.5 at.%; while in the near-surface region of the grains, the segregation effect continuously enriches element X, with concentrations reaching levels far higher than those in the bulk phase. As the sintering time increases, this concentration gradient gradually tends to a steady state, forming a stable distribution with increasing concentration from the inside to the surface.

[0091] In some embodiments of the present invention, in S3, the amount of lithium source and the second compound containing element X added satisfies the following condition: the molar ratio of element X to Co is (0.005:1) to (0.02:1).

[0092] The molar ratio refers to the ratio of the total amount of X element added in step S3 to the amount of cobalt element in the first structure obtained in step S2. The reason for controlling this ratio within the range of (0.005:1) to (0.02:1) is that if the molar ratio of the added X element to cobalt is less than 0.005:1, the amount of added X element is insufficient to form a continuous and complete crystalline compound coating layer of the third structure on the surface of the second structure. The coating layer may exist in a discontinuous island-like form, failing to achieve complete chemical protection of the substrate. If the molar ratio is greater than 0.02:1, the excessive X element will cause the thickness of the third structure coating layer to exceed the upper limit of 20 nm. Simultaneously, an excessively thick coating layer will increase the diffusion barrier of lithium ions, reducing the rate performance and specific capacity of the material. Furthermore, excessive X element may form an inactive impurity phase on the surface. Within the ratio range of (0.005:1) to (0.02:1), the thickness of the third structure coating layer can be controlled within the preferred range of 2nm to 20nm, which ensures complete coverage and chemical protection of the substrate without significantly hindering the interfacial transport of lithium ions.

[0093] In some embodiments of the present invention, in step S3, the mass of the crystalline compound coating layer is 0.5% to 2% of the mass of the first structural matrix.

[0094] If the mass of the coating layer is less than 0.5% of the mass of the first structure substrate, the absolute mass of the coating layer is too small, making it difficult to form a uniform, continuous, and sufficiently thick coating layer on the surface of the second structure. Incomplete coating results in insufficient protection. If the mass of the coating layer is greater than 2% of the mass of the first structure substrate, the mass ratio of the coating layer is too large. On the one hand, this significantly reduces the overall mass specific energy density of the material; on the other hand, an excessively thick coating layer will severely hinder the interfacial transport of lithium ions. This mass ratio corresponds to the thickness of the third structure and the amount of element X added. By controlling the amount of compound containing element X added in step S3, the mass and thickness of the coating layer can be adjusted.

[0095] In some embodiments of the present invention, in S1 and S3, element X is at least one of Al, P, Zr, Ti, La, and Y.

[0096] These elements possess suitable ionic radii and strong oxygen affinity, enabling them to form stable doping sites in the lithium cobalt oxide lattice, which is beneficial for constructing a coherently matched chemical bond network. Al and P elements have small ionic radii, readily entering cobalt sites or interstitial sites in the lithium cobalt oxide lattice, with P being the most readily incorporated. 5+ Existing in the form of oxygen, it possesses high diffusion and migration capabilities within the crystal lattice. Zr, Ti, La, and Y elements have high oxygen affinity, enabling them to form stable XO chemical bonds and enhance interfacial bonding strength. Taking P as an example, during high-temperature sintering, P... 5+ Diffusion from the particle surface to the interior, constrained by the layered structure of CoO6 octahedra, affects P. 5+ The lattice has limited capacity, and the near-surface region quickly reaches solid solution saturation. Subsequent diffused phosphorus (P) cannot be contained by the lattice and is forced to segregate at the grain surface and grain boundaries. With prolonged sintering time, the P concentration in the bulk phase is constrained to a low level by the solid solution limit, while the surface region continues to accumulate P due to segregation, ultimately forming a steady-state gradient distribution from high concentration on the surface to low concentration in the bulk. The key feature of this gradient structure is that the concentration of x in the bulk phase is controlled below the solid solution limit, without affecting the integrity of the layered structure; while the x-rich region on the surface acts as a functional layer for inducing and chemically bridging subsequent crystalline compound coating layers.

[0097] This application also provides a positive electrode sheet, which includes the aforementioned lithium cobalt oxide positive electrode material, or includes lithium cobalt oxide positive electrode material prepared by the aforementioned preparation method.

[0098] In this embodiment, the positive electrode sheet includes a positive current collector and a positive active material coated on at least one side of the positive current collector.

[0099] This application does not limit the selection of the positive electrode current collector, which can be selected according to actual needs, such as aluminum foil. The positive electrode active material layer in this application embodiment can be coated on at least one side of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material selected from positive electrode materials such as lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium-rich manganese-based oxide, lithium nickel manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate.

[0100] In one specific embodiment, the positive electrode active material layer further includes a positive electrode conductive agent and a positive electrode binder. The positive electrode conductive agent includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene. The positive electrode binder includes at least one of polyvinylidene fluoride, polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.

[0101] This application also provides a lithium battery, which includes the aforementioned positive electrode.

[0102] The battery in this application embodiment can be formed by winding or stacking positive electrode sheets, negative electrode sheets and separator. Specifically, the positive electrode sheets, separator and negative electrode sheets are stacked in sequence, so that the separator is in the middle of the positive and negative electrodes to play a role in isolation. Then the stacked electrode sheets and separator are wound or stacked to obtain the battery.

[0103] In this embodiment, the negative electrode sheet includes a negative current collector and a negative active material coated on at least one side of the negative current collector.

[0104] This application does not limit the selection of the negative electrode current collector; it can be selected according to actual needs, such as copper foil. The negative electrode active material layer of this application includes a negative electrode active material, a negative electrode binder, and a negative electrode conductive agent. The negative electrode active material includes carbon materials, silicon materials, or silicon-carbon / graphite composite negative electrode materials. The silicon-carbon / graphite composite negative electrode material includes silicon-carbon composite materials and surface-modified graphite materials. The silicon-carbon composite material includes silicon materials and carbon materials. This application does not limit the selection of carbon materials; it can be selected according to actual needs, such as graphite, carbon black, hard carbon, soft carbon, etc. This application does not limit the selection of silicon materials; it can be selected according to actual needs, such as silicon oxide, pre-lithiated silicon oxide, pre-magnesiated silicon oxide materials, silicon-carbon composite materials, elemental silicon, etc. The negative electrode binder of this application includes one or more of polyacrylic acid, polydopamine, and carboxymethyl cellulose. Polypropylene compounds refer to polypropylene derivatives, such as polyacrylic acid, polyacrylonitrile, polyacrylamide, and polymethyl acrylate. The negative electrode conductive agent includes one or more of carbon nanotubes, graphene, and vapor-grown carbon fibers.

[0105] The electrolyte in this embodiment includes an organic solvent, a lithium salt, and additives.

[0106] In the embodiments of this application, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium difluorooxalate borate (LiODFB), lithium bis(oxalate borate) (LiBOB), lithium difluorodioxalate phosphate (LiDFOP), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorophosphate (LiPOF2), and the concentration of the lithium salt can be from 0.4 mol / L to 2.2 mol / L.

[0107] In the embodiments of this application, the organic solvent includes at least one selected from ethylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, ethyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.

[0108] In one specific embodiment, the diaphragm includes a porous sheet-like or non-woven material with excellent liquid retention properties. The diaphragm includes resin or glass fiber diaphragm materials, which include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, etc.

[0109] This application does not impose any particular limitation on the specific type of battery; it can be a secondary battery, a power battery, an energy storage battery, etc. The battery casing can be used to encapsulate the battery cell and electrolyte. The battery casing can be a hard casing, such as a hard plastic casing, an aluminum casing, or a steel casing. It can also be a pouch battery, such as a pouch-type pouch. The material of the pouch can be aluminum-plastic film or plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate. This application does not impose any particular limitation on the shape of the battery; it can be cylindrical, square, or any other arbitrary shape.

[0110] Corresponding to the aforementioned application function implementation method embodiments, this application also provides an electronic device and corresponding embodiments.

[0111] This application also provides an electronic device, including the aforementioned battery.

[0112] For example, the aforementioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), low-altitude electrical equipment (such as drones, vertical take-off and landing aircraft, flying cars, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.

[0113] To further understand the present invention, the following embodiments are provided to illustrate the present application. These embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0114] I. Preparation of Lithium Cobalt Oxide Cathode Material Example 1 S1: Na₂CO₃, Co₃O₄, and NH₄H₂PO₄ were mixed in a stoichiometric ratio of 0.8:1:0.005 and sintered at 850°C for 36 hours in air to obtain P₂ phase Na. 0.7 CoO2.

[0115] S2: The above powder is mixed with LiOH / LiCl mixed lithium salt at a Co:Li molar ratio of 1:2 (where the mixed lithium salt LiOH:LiCl molar ratio is 1:1), and the mixture is exchanged in a reactor at 120°C for 20 hours. After washing and drying, the O2 phase LiCoO2 is obtained.

[0116] S3: Disperse the product from step 2 in H2O, add stoichiometric amounts of LiOH·H2O and H3PO4 (Co:Li:P=1:0.01:0.01), stir and evaporate to dryness at 110℃, and sinter in air at 200℃ for 6 hours to obtain the final product.

[0117] The prepared product was subjected to physicochemical property testing to detect the characteristics of the first, second, and third structures.

[0118] XPS was performed using a ULVAC PHI 5000 Versaprobe Ⅲ instrument with Ar cluster ion gun etching; XRD was performed using a BRUKER D8 ADVANCE instrument with a scan rate of 0.01° step size and 0.5 s / step; SEM was performed using a NOVA NANOSEM450 instrument with a voltage range of 5~20 kV.

[0119] Other embodiments and comparative examples The remaining embodiments and comparative examples are basically the same as in Embodiment 1, with the differences shown in Table 1.

[0120] Table 1

[0121] Note: Gradient-increasing distribution thinning / thickening refers to compressing (thinning) or expanding (thickening) the physical thickness range occupied by the internal concentration gradient while maintaining the internal concentration gradient trend and specific concentration values. For example, if the original concentration change from 10% to 90% occurred within a 100nm thickness, "thinning" would compress it to within 50nm to achieve the same 10%→90% change; "thickening" would stretch it to within 200nm.

[0122] II. Performance Testing The following performance tests were conducted on each embodiment and comparative example, and the test results are shown in Table 2.

[0123] 1. Physicochemical property tests: DSC test: DSC was performed using a NETZSCH STA 449 F3 instrument with an air flow of 20 ml / min and a temperature rise of 10 K / min.

[0124] 2. Electrochemical performance testing: The positive electrode material prepared by the above method was mixed with acetylene black and PVDF at a mass ratio of 94:3:3 to form a slurry. The slurry was then uniformly coated onto aluminum foil and cut into positive electrode sheets with a diameter of 12 mm. Lithium metal sheets were used as negative electrodes, Celgard 2500 was used as separators, and a 1.2 M LiPF6 EC / EMC / DMC (volume ratio 1:2:2) solution was used as electrolyte. The CR2016 button cell was assembled in an argon-filled glove box. The voltage range of the test was 3~4.63V, and the test temperature was 25℃.

[0125] First week of charge and discharge at 25℃: The test was conducted in a NEWARE test cabinet at 25℃ with a voltage window of 3~4.63V. The specific capacity and median voltage were obtained by charging and discharging for one week using a current density of 20 mA / g. Mass energy density = specific capacity × median voltage.

[0126] 45℃ Cycling: The test was conducted in a NEWARE test cabinet at 45℃, with a voltage window of 3~4.63V, and 50 charge-discharge cycles were performed using a current density of 40 mA / g to obtain the capacity retention rate.

[0127] Table 2

[0128] Based on the data in Tables 1 and 2, and through comparative analysis of Examples 1 to 6 and Example 13, it can be concluded that: A comparison of Examples 1, 2, 3, 4, 5, and 6 shows that using different X elements from Al, P, Zr, Ti, La, and Y provided in this application can achieve the triple synergistic function of gradient doping, co-lattice transition layer, and chemical bond bridging to varying degrees. Among them, P element doping effect is the best, followed by Al and Ti. The overall effect of Zr, La, and Y is slightly lower, but all are better than the schemes in the comparative examples without the addition of X element.

[0129] Example 13 uses Mg as the X element, which is not within the range of Al, P, Zr, Ti, La, and Y provided in this application. Compared with Examples 1 to 6, the overall performance of Example 13 is worse. Analysis shows that although Mg can enter the lithium cobalt oxide lattice, its ionic radius and oxygen affinity differ significantly from the elements selected in this application, making it difficult to form an effective enrichment gradient distribution on the surface and unable to induce the formation of a eutectic transition layer and XO chemical bond network. As a result, the three-layer core-shell structure cannot be completely constructed, and the overall performance is lower than that of Examples 1 to 6.

[0130] A comparative analysis of Examples 1, 7, and 8 shows that: A comparison of Examples 1, 7, and 8 shows that as the surface doping concentration of the first structure increases, the first-cycle discharge specific capacity decreases, but the peak DSC exothermic temperature increases. This demonstrates that an appropriate concentration of X doping in the surface layer stabilizes the P63mc structure by suppressing lattice oxygen escape and cobalt dissolution, while an appropriate low concentration of doping in the bulk phase avoids severe capacity loss, achieving a balance between structural stability and capacity.

[0131] A comparative analysis of Examples 1, 9, and 10 shows that: A comparison of Examples 1, 9, and 10 shows that as the thickness of the second structure increases, the first-cycle discharge specific capacity first increases and then decreases. Example 10 has the highest cycle retention rate but a significant decrease in specific capacity, while Example 1 achieves the optimal balance between specific capacity and cycle retention rate. This demonstrates that a moderate eutectic transition layer thickness (5nm~30nm) can effectively buffer the lattice mismatch stress between the first and third structures and reduce the lithium-ion migration barrier, while excessive thickness increases the interfacial impedance.

[0132] A comparative analysis of Examples 1, 11, and 12 shows that: A comparison of Examples 1, 11, and 12 shows that a crystalline compound coating layer with a thickness in the range of 2 nm to 20 nm can form a uniform and complete coating layer that effectively isolates the electrolyte without significantly hindering the interfacial transport of lithium ions.

[0133] A comparative analysis of Examples 14 and 15 shows that: A comparison of Examples 14 and 15 with Example 1 shows that adjusting the distribution of the P concentration gradient can simultaneously achieve both high capacity and high stability.

[0134] A comparative analysis of Examples 16 and 17 shows that: A comparison of Examples 16 and 17 with Example 1 shows that the high-temperature sintering conditions in the S1 stage directly affect the diffusion behavior and gradient distribution morphology of element X in the P2 phase sodium cobalt oxide lattice. Example 16, due to its low sintering temperature, resulted in incomplete solid-state reaction and insufficient establishment of the element X gradient distribution, leading to poor overall performance. Example 17, due to its high sintering temperature, experienced abnormal grain growth, uneven grain size distribution, and a large range of element X gradient distribution, also resulting in poor overall performance. Example 1, employing moderate sintering conditions, achieved the most ideal element X gradient distribution and the best overall performance.

[0135] A comparative analysis of Examples 18 and 19 shows that: A comparison of Examples 18 and 19 with Example 1 shows that the low-temperature sintering temperature in the S3 stage has a significant impact on the in-situ formation quality of the second and third structures. In Example 18, due to the excessively low sintering temperature, the activation energy of the surface chemical reaction was insufficient, resulting in incomplete formation of the second and third structures, low crystallinity of the coating layer, and poor overall performance. In Example 19, due to the excessively high sintering temperature, although the surface reaction was sufficient, it approached the threshold of the P63mc to R-3m phase transition, causing irreversible phase transitions in part of the first structure, leading to poor overall performance. Example 1, using a moderate sintering temperature, ensured both sufficient surface chemical reaction and strict protection of the metastable P63mc phase of the first structure, resulting in the best overall performance.

[0136] Taking Example 1 as an example: In terms of structural characterization: XRD patterns ( Figure 2 The results show that the main diffraction peaks of the obtained material are located at positions such as 2θ=18.6°, which are highly consistent with the standard first structure P63mc space group LiCoO2, and there are no impurity phase peaks. At the same time, weak Li3PO4 characteristic peaks appear at positions such as 2θ=22.3° and / or 23.4°, indicating that the third structure is crystalline lithium phosphate, confirming that the obtained material has the composite diffraction characteristics of both the hexagonal layered structure of P63mc space group and the orthorhombic structure of Pmn21 space group.

[0137] XPS etching profile ( Figure 3 This demonstrates that the P element content increases systematically from the inside out, verifying the successful construction of the gradient doping structure.

[0138] DSC curve ( Figure 4The results show that the main exothermic peak decomposition onset temperature of the material in Example 1 is 298.2℃, and the total exothermic amount is 61.1 J / g. In contrast, the main exothermic peak decomposition onset temperature of the material in Comparative Example 1 is only 273.5℃, and the total exothermic amount is 109.0 J / g. The thermal stability of the material in Example 1 is improved by approximately 25℃, and the total exothermic amount is significantly reduced, demonstrating that the three-layer core-shell structure of this invention effectively suppresses the phase transition, oxygen release reaction, and thermodynamic instability of the O2 phase at high temperatures.

[0139] SEM photos ( Figure 5 The results show that the particles are spherical or polyhedral in shape, with a particle size D50 of approximately 5 μm. The particles are uniform, with no obvious cracks or flaking on the surface, and the coating layer is uniform and continuous. The combined structural characterization and electrochemical testing results confirm the effectiveness and consistency of the three-layer core-shell structure design of this invention.

[0140] Regarding electrochemical performance: Figure 6 For the comparison of the first-week charge-discharge curves of Example 1 and Comparative Example 1, Example 1 has a reversible specific capacity of 257.6 mAh / g and a mass energy density of 1044.5 Wh / kg at a 0.1C rate and 3~4.63V, which is much higher than Comparative Example 1's 238.5 mAh / g and 950.4 Wh / kg.

[0141] Figure 7 For the comparison of the 45°C cycling performance of Example 1 and Comparative Example 1, after 50 cycles at high temperature, the capacity retention rate of Example 1 was 77.1%, while that of Comparative Example 1 was only 40.8%, which proves that the multilayer epitaxial structure of Example 1 plays a crucial role in improving the cycling stability.

[0142] Although this application has been described with reference to preferred embodiments, those skilled in the art will understand that various changes can be made and equivalents can be substituted for the elements, as long as they do not depart from the scope of this application. Furthermore, many modifications can be made to adapt particular situations or materials to the teachings of this application, as long as they do not depart from the essential scope of this application. Therefore, this application is not intended to be limited to the specific embodiments disclosed as the best mode of carrying out this application as conceived, but rather this application will include all embodiments falling within the scope of the appended claims.

[0143] All scopes disclosed in this application include endpoints, and endpoints can be combined with each other.

[0144] The various embodiments of this application have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or improvement of the technology in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.

Claims

1. A lithium cobalt oxide cathode material, characterized in that, The lithium cobalt oxide cathode material has a three-layer core-shell structure, including: A first structure, wherein the first structure is a lithium cobalt oxide matrix containing at least the P63mc space group; A second structure, which at least partially covers the first structure, includes a co-lattice transition layer of one or more structures in the space groups Fd-3m, Fm-3m, R-3m, and P63mc. A third structure, which at least partially covers the second structure, comprises a crystalline compound of one or more of the space groups R-3m, Pnma, Pmn21, and C2 / c. The first, second, and third structures all contain the same element X. The concentration of element X increases progressively from the distal end to the proximal end of the second structure within the lattice of the first structure. The second structure forms a Co-OX coherent match with the first structure via an XO chemical bond network and also forms an XO bond with the third structure. The element X is at least one of Al, P, Zr, Ti, La, and Y. In the first structure, the concentration of element X from the distal end to the proximal end of the second structure is 0~2 at.%; the total concentration of element X in the lithium cobalt oxide cathode material is less than 5 at.%; the thickness of the second structure is 5nm~30nm; the thickness of the third structure is 2nm~20nm; the second structure is a Li-Co-XO structure containing element X, where element X occupies a portion of the lattice sites; the second structure and the third structure form a continuous XOX or XO-Li chemical bond network.

2. A method for preparing the lithium cobalt oxide cathode material as described in claim 1, characterized in that, Includes the following steps: S1. Sodium source, cobalt source and first compound containing element X are mixed in stoichiometric ratio and sintered at high temperature under first set conditions to obtain sodium cobaltate of phase P2. The concentration of element X in sodium cobaltate of phase P2 increases in a gradient from the inside to the outside. S2. The product obtained in S1 is mixed with lithium salt and subjected to ion exchange reaction under the second set conditions to obtain lithium cobalt oxide with a P63mc space group structure containing an X element gradient distribution, which is used as the first structure. S3. The product obtained in S2 is dispersed in a solvent, a lithium source and a second compound containing element X are added, and after stirring and evaporation, it is subjected to low-temperature sintering under a third set condition. A co-lattice transition layer containing at least one or more of the space groups Fd-3m, Fm-3m, R-3m, and P63mc is formed in situ on the surface of the first structure as the second structure. At the same time, a crystalline compound coating layer containing at least one or more of the space groups R-3m, Pnma, Pmn21, and C2 / c is formed in situ on the surface of the second structure as the third structure. The first compound containing element X and the second compound containing element X are each independently selected from compounds containing element X, and the two contain the same element X.

3. The preparation method according to claim 2, characterized in that, The first set conditions include: a high-temperature sintering temperature of 720℃~880℃ and a high-temperature sintering time of 18h~48h; and / or, the second set conditions include: an ion exchange temperature of 80℃~140℃ and an ion exchange time of 8h~72h; and / or, in S3, the stirring and drying temperature is 100℃~130℃.

4. The preparation method according to claim 2, characterized in that, The low-temperature sintering temperature in the third set condition is lower than the temperature at which the P63mc space group structure undergoes an irreversible phase transition to the R-3m space group structure.

5. The preparation method according to claim 4, characterized in that, The third set conditions include: the temperature of low-temperature sintering is 150℃~250℃, and the time of low-temperature sintering is 4h~24h.

6. The preparation method according to claim 2, characterized in that, In step S1, the stoichiometric ratios of the sodium source, the cobalt source, and the first compound containing element X satisfy the following conditions: the molar ratio of Na:Co:X is (0.6~0.9):1:a, 0<a≤0.1; and / or, In S1, the equilibrium solid solubility of element X in the lattice of sodium cobaltate in the P2 phase is less than 0.5 at.%; and / or, In step S3, the amounts of the lithium source and the second compound containing element X added satisfy the following conditions: the molar ratio of element X to Co is (0.005:1) to (0.02:1); and / or, In step S3, the mass of the crystalline compound coating layer is 0.5% to 2% of the mass of the first structural matrix; and / or, In S1 and S3, the X element is at least one of Al, P, Zr, Ti, La, and Y.

7. A positive electrode sheet, characterized in that, The positive electrode sheet comprises the lithium cobalt oxide positive electrode material as described in claim 1, or comprises the lithium cobalt oxide positive electrode material prepared by any one of claims 2 to 6.

8. A lithium battery, characterized in that, The lithium battery includes the positive electrode as described in claim 7.